Relationship Between Knowledge and Compliance of Iron Tablet Consumption During Menstrual Cycle Among Nursing Students - Feby Margareta; Sulastri Sulastri (GLOBAL HEALTH SCIENCE GROUP, 2024)
Adolescence in girls is marked by increased iron requirements due to the development of sexual organs and menstruation, making them more susceptible to anemia. Increasing compliance with taking iron tablets is very important to reduce the risk of anemia and maintain the health of adolescent girls. The purpose of this study was to determine the relationship between knowledge and compliance with taking iron tablets during the menstrual cycle. The method used was quantitative observational analytical research with a cross-sectional approach, at the Muhammadiyah University of Surakarta in July 2024. The sampling technique was total sampling, namely 145 nursing students from the Muhammadiyah University of Surakarta class of 2023. Data collection was carried out using a demographic data questionnaire, knowledge of iron supplements and compliance with taking medication (MMAS-8). Univariate data analysis and bivariate statistical tests used Spearman rank. The results of data processing showed that the level of knowledge of the respondents was mostly in the moderate category with a percentage of 50.3% (73 respondents). The level of compliance was in the low category with a percentage of 66.2% (96 respondents). Based on the analysis using Spearman rank, a significance value of 0.001 was obtained, which means that there is a relationship between the level of knowledge about iron tablets and compliance in taking iron tablets during menstruation in female students, while the correlation coefficient is 0.282, which means that there is a significant relationship between the level of knowledge about iron tablets and compliance in taking iron tablets during menstruation in female students.